2021
DOI: 10.1016/j.jclinepi.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity is associated with frailty in community-dwelling older adults: A systematic review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 68 publications
7
34
0
Order By: Relevance
“…Previous studies have shown that having an unhealthy lifestyle is associated with frailty [ 16 18 ]. Studies focused on specific lifestyle factors as smoking [ 20 ], excessive alcohol use [ 24 ], poor dietary habits [ 26 ], and low physical activity [ 29 ], provided evidence that these individual factors had an effect on frailty. However, frailty was predominantly defined as a biological concept, consisting of physical limitations that older people may have, mostly represented by the phenotype of frailty [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that having an unhealthy lifestyle is associated with frailty [ 16 18 ]. Studies focused on specific lifestyle factors as smoking [ 20 ], excessive alcohol use [ 24 ], poor dietary habits [ 26 ], and low physical activity [ 29 ], provided evidence that these individual factors had an effect on frailty. However, frailty was predominantly defined as a biological concept, consisting of physical limitations that older people may have, mostly represented by the phenotype of frailty [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review carried out by Tolley et al aimed to synthesize the available evidence with regard to the associations of objectively measured habitual physical activity and frailty in community-dwelling older people. This review, based on 23 articles totaling 7,696 participants, concludes that objective measures of physical activity are associated with frailty, regardless the operational definition of frailty [ 29 ]. Based on four studies, a meta-analysis also showed that physical activity probably prevents frailty [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while age-specific incidence rates vary, the highest rates observed are in the 85 to 89 age group, for both males and females [ 1 ]. Advanced age is associated with recognised prognostic factors including co-morbidity [ 2 ], sarcopenia [ 3 ] and frailty [ 4 ]. Therefore, decisions on whether to embark on potentially curative treatment are often complex in older adults with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the association between sedentary time and frailty monitored by wearable devices was inconsistent. A recently published systematic review shows that sedentary time does not affect the prevalence of frailty [32,33]. This may be due to the inconsistency in the measurement of frailty and the population.…”
Section: Discussionmentioning
confidence: 99%